Simulation of spatiotemporal patterns of habitat quality and driving mechanism in Anhui province, China - Zhang, Guanjin; Roslan, Siti Nur Aliaa; Quan, Ling; Yuan, Ping (Frontiers in Environmental Science, 2023)
Habitat quality is an important basis for human well-being and sustainable development. It is of great significance to the conservation of regional ecology and sustainable use of land resources. This paper examined Anhui Province, China, through topo-graphic data, climate data, human activity data, and land use data from 2000, 2010, and 2020. To reveal the habitat quality impact mechanisms, the paper assessed the province’s spatiotemporal evolution characteristics of habitat quality by the Patch-generating Land Use Simulation (PLUS) model, Integrated Valuation of Ecosystem Services and Trade-offs (INVEST) model, and geo-graphic probe model. The results showed that: (1) From 2000 to 2020, Paddy field, Dryland, and Wooded land covered 70% of the study area. From 2000 to 2020, the integrated land use dynamic attitude was 0.51%, with active changes in the Paddy field, Dryland, and open Wooded land and a continuous increase in dynamic attitude. Compared to 2020, the spatial distribution characteristics of land use types in 2030 remain largely unchanged. However, Paddy fields and Drylands still show an increasing trend, while Wooded land, Reservoir ponds, and Urban land demonstrate a small decreasing trend. All other land types remain unchanged; (2) Secondly, between 2000 and 2020, habitat quality gradually decreased, while the percentage of poor habitat quality increased by 1.47% and the percentage of worse habitat quality decreased by -1.41%. All other classes exhibited a small decreasing trend; the mean habitat quality decreased by 0.01 compared to 2020 in 2030, and was mainly distributed in the southwestern and eastern edges of the province; and (3) DEM, aspect, precipitation, and evapotranspiration have a high explanatory power for habitat quality, while the variable Places has significantly increased its explanatory power for habitat quality between 2010 and 2020. Natural factors laid down the graded distribution pattern of habitat quality, and the location and intensity of human activities drove the evolution of habitat quality. Analyzing the mechanism behind habitat quality in Anhui Province provides a theoretical basis for ecological restoration and ecological planning.